Lung Epithelial TRPA1 Mediates Lipopolysaccharide-Induced Lung Inflammation in Bronchial Epithelial Cells and Mice - Ko, Hsin-Kuo; Lin, An-Hsuan; Perng, Diahn-Warng; Lee, Tzong-Shyuan; Kou, Yu Ru (Frontiers in Physiology, 2020)
Toll-like receptor (TLR) 4 was originally thought to be the sole pattern recognition receptor for lipopolysaccharide (LPS). Transient receptor potential ankyrin 1 (TRPA1), a Ca2+-permeant channel, has been suggested as a non-TLR receptor membrane-bound sensor of LPS. We recently reported that TRPA1 is expressed in lung epithelial cells (LECs) and mediates lung inflammation induced by cigarette smoke. However, the role of TRPA1 in LPS-induced lung inflammation has not been conclusively defined, and its underlying cellular mechanisms remain unclear. In this study, our in vitro results showed that LPS sequentially produced a cascade of events, including the elevation of intracellular Ca2+, the activation of NADPH oxidase, increase in intracellular reactive oxygen species (ROS), the activation of mitogen-activated protein kinase (MAPK)/nuclear factor-B (NF-κB) signaling, and the induction of IL-8. The increase in intracellular Ca2+ was inhibited by HC030031 (a TRPA1 antagonist) but was unaffected by TAK-242 (a TLR-4 inhibitor). The activation of NADPH oxidase was prevented by its inhibitor apocynin, EGTA (an extracellular Ca2+ chelator), and HC030031. The increase in intracellular ROS was attenuated by apocynin, N-acetyl-cysteine (NAC, a ROS scavenger), EGTA, and HC030031. The activation of the MAPK/NF-κB signaling was halted by NAC, EGTA, and HC030031. IL-8 induction was suppressed by HC030031 and TRPA1 siRNA, and further reduced by the combination of HC030031 and TAK-242. Our in vivo studies showed that trpa1-/- mice displayed a lower level of LPS-induced lung inflammation compared with wild-type mice based on the alleviation of increased vascular permeability, the reduction of inflammatory cell infiltration, the decrease in inflammatory cytokine levels, the reduction of oxidative stress, and the activation of MAPK signaling. Thus, in LECs, LPS may activate TRPA1, which leads to an increase in Ca2+ influx. The increased intracellular Ca2+ contributes to the activation of NADPH oxidase and results in increased intracellular ROS, which activates MAPK/NF-B signaling and leads to IL-8 induction. This mechanism may possibly be at work to induce lung inflammation in mice.